Free International Trade Impact On The Growth Of Small And Medium Enterprises: Analytical Descriptive Study - Abdullah Al Ghaithi, Issa Khamis; Salleh, Ahmad Zaki; Hassan, Zulkifli (Perdana: International Journal of Academic Research, 2019)
Economists combine the great role of small and medium-sized enterprises in advancing the development of all countries, whatever their economic situation, and the different economic structures and different levels of growth. This sector, despite its great importance, faces many challenges; mostly the unfair competition of large companies, especially foreign companies, which stand in the way of the growth of these projects, especially after the World Trade Organization (GATT) establishment and trade liberalization. In order for these projects to play true role, they must be supported by policies that contribute to their success. The role of laws and legislation contributes to control the competition, regulates the work of such projects, protects them and exploits foreign investments. The study discussed the significance of SMEs, the characteristics that characterize them, as well as the challenges facing these projects, the principles of the WTO and the implications of trade liberalization. The study concluded that accession to the World Trade Organization is no longer an option but a reality imposed by the global economy. The WTO Agreement covered all economic activity; productive, service, logistics, information and financial flows. States are unable to take any step to protect national goods in the competition for foreign goods. The study recommended providing government support to small and medium-sized enterprises in developing countries and requiring large national companies to support SMEs technically. ملخص البحث يجمع خبراء الاقتصاد على الدور الكبير للمشروعات الصغيرة والمتوسطة في دفع عجلة التنمية لجميع البلدان، مهما كان الوضع الاقتصادي لها، ومهما اختلفت الهياكل الاقتصادية وتباينت درجات نموها. إلا إنّ هذا القطاع رغم أهميته الكبيرة يواجه العديد من التحديات؛ ومن أبرزها المنافسة غير العادلة من قبل الشركات الكبرى وبخاصة الشركات الأجنبية، التي تقف حجر عثرة أمام نمو هذه المشروعات لاسيما بعد تأسيس منظمة التجارة العالمية (الجات) وتحرير التجارة. ولكي تقوم هذه المشروعات بدورها الحقيقي؛ فلا بدَّ من أنْ تدعمها سياسات تسهم في نجاحها، ويأتي دور القوانين والتشريعات في تسهم في ضبط المنافسة، وتعمل على تنظيم عمل تلك المشروعات وحمايتها، واستغلال الاستثمارات الأجنبية. ناقشت الدراسة أهمية المشروعات الصغيرة والمتوسطة، والسمات التي تميزها. كذلك التحديات التي تواجه هذه المشروعات، والمبادئ التي تعمل وفقها منظمة التجارة العالمية والآثار المترتبة على تحرير التجارة. خلصت الدراسة إلى نتائج: أنّ الانضمام لمنظمة التجارة العالمية لم يعد خياراً وإنما أصبح واقعاً تفرضة مقتضيات الواقع الاقتصادي العالمي. غطت اتفاقية منظمة التجارة العالمية جميع أوجه النشاط الاقتصادي ليشمل الأنشطة الإنتاجية والخدمية، والتموينية، والمعلوماتة، والتدفقات المالية. أصبحت الدول عاجزة عن اتخاذ أية إجراءات لحماية السلع الوطنية أو دعمها في منافسة السلع الأجنبية. أوصت الدراسة بتوفير الحماية للمشروعات الصغيرة والمتوسطة في البلدان النامية وتوفير الدعم الحكومي لها، وإلزام الشركات الوطنية الكبيرة بدعم الشركات الصغيرة والمتوسطة فنياً، وإيجاد التشريعات التي تنظم عمل ذلك القطاع.